The Preparation and Absolute Configurations of Enantiomerically Pure C4-Symmetric Tetraalkoxyresorcin[4]arenes Obtained from Camphorsulfonate Derivatives - Buckley, B.; Page, P.; Chan, Y.; Heaney, H.; Klaes, M.; Mcildowie, M.; McKee, V.; Mattay, J.; Mocerino, Mauro; Moreno, E.; Skelton, B.; White, A. (Wiley-VCH Verlag GMBH, 2006)
The preparation of a series of diastereoisomeric tetracamphorsulfonates derived from racemic tetramethoxyresorcin[4]arenes was achieved by reactions with an excess of (S)‐(+)‐10‐camphorsulfonyl chloride in pyridine followed by isolation using flash chromatography. Tetradeprotonation of a number of tetramethoxyresorcin[4]arenes using n‐butyllithium in tetrahydrofuran, followed by reactions using (S)‐(+)‐10‐camphorsulfonyl chloride, gave the same tetracamphorsulfonates. Mono‐, di‐ and tricamphorsulfonates were also prepared following selective deprotonation. In the reactions with tetraisopropyloxy‐ and tetracyclopentyloxyresorcin[4]arenes, only the mono‐ and dicamphorsulfonates were formed. X‐ray crystallographic analysis established the absolute configurations of three diastereoisomerically pure tetracamphorsulfonates, including a diastereoisomer prepared from 6,12,18,24‐tetramethoxy‐2,8,14,20‐tetrakis(2‐methylpropyl)resorcin[4]arene. An additional pair of diastereoisomers was also prepared using (R)‐(–)‐10‐camphorsulfonyl chloride and 6,12,18,24‐tetramethoxy‐2,8,14,20‐tetrakis(2‐methylpropyl)resorcin[4]arene, for one of which the structure was confirmed by an additional X‐ray structure determination. Hydrolytic removal of the camphorsulfonyl residue(s) from the various diastereoisomers gave enantiomers of known absolute configurations. In some cases, the chiral nonracemic tetraalkoxyresorcin[4]arenes were converted into known tetrabenzoxazine derivatives by using N,N‐bis(methoxymethyl)[(S)‐(–)‐(α‐methylbenzyl)]amine in thermal or microwave‐assisted reactions.